A variant within FGF1 is associated with Alzheimer's disease in the Han Chinese population. Issue 2 (24th January 2014) - Tao, Qing‐Qing; Sun, Yi‐Min; Liu, Zhi‐Jun; Ni, Wang; Yang, Ping; Li, Hong‐Lei; Lu, Shen‐Ji; Wu, Zhi‐Ying
Abstract Alzheimer's disease (AD) is the most common neurodegenerative disorder characterized by the accumulation of amyloid beta (Aβ) plaques and Tau‐containing neurofibrillary tangles in vulnerable brain areas. The progression of AD is well correlated with hippocampal neuron loss which highly suggests genes associated with neuron survival would be important for AD pathogenesis. According to the recent results of genome‐wide association studies (GWAS) and other reported studies, we selected two single nucleotide polymorphisms (SNPs), rs3765728 within tumor protein p73 (P73), and rs34011 within fibroblast growth factor 1 (FGF1), both genes were related to neuron survival. We analyzed the distribution of rs3765728 and rs34011 in 1, 083 Chinese subjects including 429 unrelated sporadic AD patients and 654 unrelated age and gender‐matched control subjects. We found that the genotype distribution of rs34011 was significantly different between AD and control group (χ2 = 9.048, df = 2, P = 0.011). Logistic regression manifested the risk of AD increased in TT genotype carriers in total subjects (Wald = 8.892, df = 1, P = 0.003, odds ratio [OR]:2.009, 95% confidence interval [95%CI]: 1.270–3.178). This effect was also found in APOE ϵ4 carrier group (Wald = 7.844, df = 1, P = 0.005, OR: 4.201, 95%CI: 1.539–11.472), suggesting the rs34011 has a synergetic effect of APOE on AD risk. However, no association was observed between rs3765728 and AD in the Han Chinese population (χ2 = 0.431, df = 2, P = 0.806). © 2014 Wiley Periodicals, Inc.